“The Righteous and Reasonable Ambition to Become a Landholder”: Land and Racial Inequality in the Postbellum South - Miller, Melinda C. (The Review of Economics and Statistics, 2020)
This paper identifies an exogenous variation in post–Civil War policy to examine the effect of land reform on racial inequality. The Cherokee Nation, located in what is now Oklahoma, permitted slavery and joined the Confederacy in 1861. During postwar negotiations, the Cherokee Nation agreed to provide free land for its former slaves. Using linked data that follow former slaves in the Cherokee Nation from 1880 to 1900, I find that racial inequality was lower in the Cherokee Nation in both 1880 and 1900. Land and the associated increase in incomes may have facilitated investment in both physical and human capital.